Audit Report Lag With the Public Accounting Firm’s Reputation as Moderation - Saftiana, Yulia; Safitri, Rika Henda; Sulastri, Sulastri; Azwardi, Azwardi; Anggelena, Vina (Politeknik Ganesha Medan, 2024)
This study examines the impact of audit quality, profitability, and solvency on audit report lag, with PAF's reputation acting as a moderating factor in LQ45 companies. Panel data analysis, combining time series and cross-sectional data, was conducted on all LQ45 companies over the period 2017-2021, using purposive sampling. Quantitative analysis employing panel data regression analysis through Eviews 10 software was employed. The findings reveal that audit quality, profitability, solvency, and PAF reputation positively and significantly influence audit report lag. Moreover, PAF reputation moderates the relationship between audit quality and audit report lag, showing a negative and significant effect. Similarly, PAF reputation moderates the relationship between profitability and audit report lag, also exhibiting a negative and significant impact. However, PAF reputation's moderation on solvency demonstrates a negative but nonsignificant effect on audit report lag. Recommendations for further research include deeper analysis of reputation as a variable, as it supports reducing audit report delays. Additionally, examining audit quality and Return on Assets in more depth using nominal variables, with audit quality measured through earnings management or discretionary accruals, is suggested. Furthermore, refining analytical techniques through transformation methods that combine linear and nonlinear forms within a regression model is recommended for future investigations.